GENESIS, NATURE, CONCEPT AND STRUCTURE OF CYBERSECURITY IN PHILOSOPHICAL DISCOURSE - Sobirov Anvar (European Science Publishing, 2024)
The intensive development of information technologies over the past 50 years has greatly changed the world in all spheres of public life. Global informatization of society is one of the dominant trends in the development of human civilization in the 21st century. "The rapid development of information technologies, the increase in the capabilities of telecommunication systems leads to the emergence of new challenges and threats committed in cyberspace." Currently, we can note a significant average annual increase in the number of incidents in the field of information security, affecting a wide range of private corporate, as well as state interests. The current situation suggests an increase in the importance of cybersecurity in the information security system.
Keywords: cybersecurity, cyberspace, cyber threat, cyber danger, information security, information space, cyber threat, information danger.